Soil-transmitted helminth infection in school age children in Sierra Leone after a decade of preventive chemotherapy interventions - Yakuba Mohamed Bah; Mohamed Salieu Bah; Jusufu Paye; Abdulai Conteh; Sam Saffa; Alie Tia; Mustapha Sonnie; Amy Veinoglou; Joseph J. Amon; Mary Hamer Hodges; Yaobi Zhang (BMC, 2019)
Abstract Background Baseline mapping of soil-transmitted helminth (STH) infections among school age children (SAC) in 2008-2009 found high or moderate prevalence in 13 of the 14 districts in Sierra Leone. Following these surveys, mass drug administration (MDA) of mebendazole/albendazole was conducted biannually at national level targeting pre-school children (PSC) aged 12-59 months and intermittently at sub-national level targeting SAC. In addition, MDA with ivermectin and albendazole for eliminating lymphatic filariasis (LF) has been conducted nationwide since 2010 targeting individuals over 5 years of age. Each MDA achieved high coverage, except in 2014 when all but one round of MDA for PSC was cancelled due to the Ebola emergency. The objective of the current study was to determine the prevalence and intensity of STH infections among SAC after a decade of these deworming campaigns. Methods Seventy-three schools in 14 districts were purposefully selected, including 39 schools from the baseline surveys, with approximately two sites from each of low, moderate and high prevalence categories at baseline per district. Fresh stool samples were collected from 3632 children aged 9-14 years (male 51%, female 49%) and examined using the Kato Katz technique. Results The prevalence of STH infections in Sierra Leone decreased in 2016 compared to 2008: Ascaris lumbricoides 4.4% (95% confidence interval [CI]: 3.7-5.1%) versus 6.6% (95% CI: 0-25%), Trichuris trichiura 0.7% (95% CI: 0.5-1.1%) versus 1.8% (95% CI: 0-30.2%), hookworm 14.9% (95% CI: 13.8-16.1) versus 38.5% (95% CI: 5.4-95.1%), and any STH 18.3% (95% CI:17.0-19.5%) versus 48.3% (CI: 5.4-96.3%), respectively. In 2016, no district had high hookworm prevalence and four districts had moderate prevalence, compared with eight and four districts respectively in 2008. In 2016, the arithmetic mean hookworm egg count in all children examined was light: 45.5 eggs per gram (EPG) of faeces, (95% CI:\ 35.96-55.07 EPG); three (0.08%) children had heavy infections and nine (0.25%) children had moderate infections. Conclusions Sierra Leone has made considerable progress toward controlling STH as a public health problem among SAC. As LF MDA phases out (between 2017 and 2021), transition of deworming to other platforms and water and sanitation strategies need to be strengthened to maintain STH control and ultimately interrupt transmission.